Elastic-plastic state of a short-circular cylinder subjected to axesymmetrical complex loading - Bay, Vu Khac (Vietnam Journal of Mechanics, 1995)
The modified method of elastic solution in the theory of elastic-plastic deformation processes had been proposed in [1]. Through the numerical solution of some elastic-plastic plane problems, the convergence, the convergence rate and the stability of this iteration method had been considered [3, 4]. In this paper, also through the numerical solution of the elastic-plastic space problem, the characters of this iteration method are considered, and the influence of complex loading processes to elastic-plastic state is confirmed.